The distribution of mosquitoes in Romania (Diptera: Culicidae). Part I: Anopheles, Aedes and Culex. Issue 13 (2002) - Nicolescu, Gabriela; Vladimirescu, Alexandru; Ciolpan, Octavian
No abstract available